Evidence for the benefit of exercise therapy in patients with type 2 diabetes - Madden KM (Dove Medical Press, 2013)
Kenneth M Madden VITALiTY (Vancouver Initiative to Add Life to Years) Research Laboratory, Division of Geriatric Medicine, Department of Medicine, University of British Columbia, Vancouver, BC, Canada Abstract: Exercise interventions are recommended in most guidelines for the treatment of type 2 diabetes. Although most guidelines suggest a combination of both aerobic and resistance training, the exact benefits of these interventions remain unclear. Although either modality alone or in combination seems to have an identical impact on glycated hemoglobin levels, resistance training and aerobic training have independent effects on other parameters of cardio-metabolic risk. This review examines the current evidence for aerobic and resistance training on glycemic control, lipid profile, body composition, vascular health, and mental health in patients with type 2 diabetes. The uncertainties surrounding exercise modality, volume and intensity are also addressed. Keywords: aerobic exercise, resistance exercise, glycemic control, cardio-metabolic risk